Importance of dental prenatal care: a narrative review (Research, Society and Development, 2021)
Introduction: In dental prenatal care, the dental surgeon will accompany the pregnant woman, recognizing her dental needs and should guide and treat the mother about oral hygiene to prevent complications such as caries, gingivitis, periodontitis, or even premature birth. This study aims to present the need for prenatal dental care, describing the importance of dental care during pregnancy. Methodology: The following descriptors and their combinations were used: “prenatal care” and “dentistry” in the SCIELO, LILACS and Academic Google databases. Initially, a total of 40 articles related to the topic were selected, among these articles, 22 were selected after full reading. Results and Discussions: Dental prenatal care needs to be expanded, but for it to grow and help future mothers about its importance and accuracy, professionals have acquired theoretical, practical and scientific knowledge on the subject. Final considerations: It was observed that the studies were positively positioned on the importance of access to dental services, guidance and early counseling on the oral health of pregnant women, emphasizing how it can directly influence the general health of the baby.